DAMPAK FLUKTUASI NILAI TUKAR RUPIAH TERHADAP EKSPOR DAN IMPOR BERAS DI INDONESIA - Safitri, Sela; Kasnelly, Sri (Jurnal Ekonomi-Qu, 2025)
Exchange rate fluctuations of the Indonesian rupiah against foreign currencies significantly impact rice trade in Indonesia. This study aims to analyze the effects of exchange rate fluctuations on rice export and import volumes and their implications for national food security. A descriptive quantitative approach was employed, using secondary data from Bank Indonesia, the Central Bureau of Statistics (BPS), and the Ministry of Trade for the period 2019-2023. The findings reveal that the weakening of the rupiah increases the cost of rice imports, while its strengthening reduces the competitiveness of rice exports. Import volumes surged significantly in 2023, whereas rice exports experienced a sharp decline. The rice trade deficit reached its peak in the past five years. Strategic policies such as enhancing domestic productivity, diversifying import sources, and stabilizing exchange rates through monetary interventions are necessary to manage these impacts. These measures are expected to achieve sustainable national food security.